РАЗВИТИЕ ИНВЕСТИЦИОННОЙ ДЕЯТЕЛЬНОСТИ ПРЕДПРИЯТИЙ НА ОСНОВЕ БЕРЕЖЛИВОГО ПРОИЗВОДСТВА (Marketing Journal, 2026)
AbstractThe article examined the development of investment activity of industrialenterprises based on lean production principles. The investment potential of enterprisesin the oil and fat industry was assessed considering production, financial, innovative,and labor factors. Optimization of production processes and reduction of losses were  substantiated as conditions for improving investment efficiency. The state of the rawmaterial base and modernization directions of the industry were analyzed. Thenecessity of applying operational performance indicators in evaluating investmentprojects was demonstrated. Digitalization and technological renewal were identified asfactors enhancing investment attractiveness. Based on the research findings, practicalrecommendations were developed to increase investment activity and ensuresustainable development of enterprises.Keywords: industry, enterprise, potential, investment, investment attractiveness,enterprise investment potential assessments, investment policy.